1982
DOI: 10.1111/j.1600-0560.1982.tb01078.x
|View full text |Cite
|
Sign up to set email alerts
|

The Histogenesis of malignant melanoma in relation to pre‐existing pigmented lesions

Abstract: One hundred and twenty-nine cases of malignant melanoma seen at Bangour General Hospital over an eleven year period were reviewed clinically and histologically. In 51 patients (39.5%) there was a history of pre-existing pigmented lesion at the site of the melanoma. In 14 cases (10.8%) histology confirmed traces of a benign melanocytic naevus. The relationships between naevus cells and malignant melanocytes are described. The patterns most frequently observed were those of intradermal naevus cells in the deeper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1

Year Published

1985
1985
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 11 publications
3
26
1
Order By: Relevance
“…8 Even more considered as unjustified and not cost-effective is the use of SDDI to detect nevus-associated melanomas at earlier stages, considering that the general rate of transformation of benign melanocytic lesions and even dysplastic nevi is extremely low. 7,[10][11][12][13][14][15][16] Yet, for many reasons, this frequency may have been overestimated or underestimated mainly because depending on the stage of development of the tumor, malignant cells may overgrow the preexisting benign melanocytic cells. 7,[10][11][12][13][14][15][16] Yet, for many reasons, this frequency may have been overestimated or underestimated mainly because depending on the stage of development of the tumor, malignant cells may overgrow the preexisting benign melanocytic cells.…”
Section: Introductionmentioning
confidence: 99%
“…8 Even more considered as unjustified and not cost-effective is the use of SDDI to detect nevus-associated melanomas at earlier stages, considering that the general rate of transformation of benign melanocytic lesions and even dysplastic nevi is extremely low. 7,[10][11][12][13][14][15][16] Yet, for many reasons, this frequency may have been overestimated or underestimated mainly because depending on the stage of development of the tumor, malignant cells may overgrow the preexisting benign melanocytic cells. 7,[10][11][12][13][14][15][16] Yet, for many reasons, this frequency may have been overestimated or underestimated mainly because depending on the stage of development of the tumor, malignant cells may overgrow the preexisting benign melanocytic cells.…”
Section: Introductionmentioning
confidence: 99%
“…If successfully implemented, this strategy would have a presumed benefit , since a reduction in pro-oncogenic oxidative stress in nevi over the course of many UV exposures would be predicted to decrease long-term (lifetime) melanoma risk. In addition, there would be less oxidative damage over time in isolated melanocytes, from which the majority of melanomas arise (2). …”
Section: Discussionmentioning
confidence: 99%
“…Although melanoma may arise directly from isolated melanocytes, a significant fraction of melanomas develop from nevi (or moles) (2), which represent congenital or acquired clonal neoplasms of melanocytes (3). Nevi are far less prevalent on sun-protected skin and their development is related to sun exposure (4), which also is the major environmental risk factor for melanoma (5).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the literature, it appears that 20–30% of melanomas appear to arise from nevi. 111113 Two studies similarly found that approximately 20% of melanomas had an histologically-associated DN, 114, 115 while another found DN remnants in association with only 7% (34/512) of melanoma cases. 116 …”
Section: Epidemiology and Natural Historymentioning
confidence: 95%